CHARACTERIZING CLAY MINERAL SUSPENSIONS USING ACOUSTIC AND ELECTROACOUSTIC SPECTROSCOPY - A REVIEW - Guerin M.; Seaman J.C. (My University, 2004)
Recently, significant advances have been made in the theory and application of acoustic and electroacoustic spectroscopies for measuring the particle-size distribution (PSD) and zeta potential (ζ potential) of colloidal suspensions, respectively. These techniques extend or replace other techniques, such as light-scattering methods, particularly in concentrated suspensions. In this review, we summarize acoustic and electroacoustic theory and published results on clay mineral suspensions, detail theoretical constraints, and indicate potential applications for the study of environmentally significant clay mineral suspensions. Using commercially available instrumentation and suspension concentrations up to 45 vol.%, acoustic spectroscopy can characterize particle sizes from 10 nm to 10 µm, or greater. Electroacoustic spectroscopy can determine the ζ potential of a suspension with a precision and accuracy in the mV range. Despite the clear potential for their use in environmental settings, to date, acoustic methods have been used mainly on clay mineral colloids with industrial application, typically combined with similar measurements such as isoelectric point (IEP) determined from shear yield stress or ζ potential from electrophoretic mobility measurements. Potential applications in environmentally relevant suspension concentrations are significant, as PSD and ζ potential are important factors influencing the transport of mineral colloids and associated contaminants through porous media. Applications include determining the effects of suspension concentration, surfactants, electrolyte strength, pH and solution composition on soil clay properties and colloidal interactions, and determining changes in PSD, aggregation and ζ potential due to adsorption or variations in the clay mineralogy.